DNA barcoding of fifteen shrimp and prawn species (Decapoda, Crustacea), living in Turkish coastal waters with phylogeographic comparisons - Utkan, Merve Aslı. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2011., 2011)
DNA barcoding is useful for the quick identification and potential discovery of species. Systematic DNA barcoding on decapods has not been done in Turkey previously, and this thesis will be a first in this regard. In this study, DNA barcoding technique is used for the determination of genetic diversity of the shrimp and prawn species in Turkish waters. Through this approach the genetic diversity of fifteen shrimp and prawn species living in Turkey was evaluated and when possible the genetic data were compared with those available from different parts of the Mediterranean and eastern Atlantic. 51 COI sequences from 12 different species, and 64 16S sequences from six different species are generated for this study. The barcoding gap using CO1 seemed to work well with these species. Out of the new sequences generated, five species had unique barcode sequences that are distinct from those found in any other species in BOLD and four 16S sequences are new (based on a comparison with GenBank). In nine species two intraspecific clades were retrieved after analyses. In eight species for which CO1 data was produced, the tree identification method worked accurately. Finally, as a part of the barcoding approach, genetic material from the studied species is now stored at Institute of Environmental Sciences Laboratories, comprising a first step towards formation of a DNA Barcoding bank for these species.
Keywords: Crustacea -- Turkey -- Genetics.; DNA -- Analysis.